Analysis of Significant Differences in The Cognitive Ability of Students With Ferris Wheel Media Based on TGT in Buffer Solution Lessons - Yudha, Sandy; Siregar, Nur' Athiyyah Muyassar (Educational Insights, 2024)
Learning media is one way to improve student learning outcomes. The Ferris wheel is one of these media that has many varied questions. It is hoped that the Ferris wheel-assisted TGT model will not only be innovative learning, but can also influence student learning outcomes. The purpose of this study is to determine the impact of the Teams Games Tournament (TGT) learning model on students' cognitive learning outcomes for the buffer solution using the Ferris wheel. A quasi-experimental design with non-equivalent groups and the posttest alone design approach is the research methodology used. Purposive sampling was employed during the sample process. All 294 students in class XI Mathematics and Natural Sciences at State High School 1 Lhokseumawe in the academic year 2022–2023 made up the population of this study. with a 50-student research sample. ways for gathering data, including tests, interviews, and observation. The research questions are evaluated with a school that is similar to the research location before being used in the study. The difficulty of the problems being examined, the discriminatory capacity, the validity, and the dependability of the tests are all taken into consideration. The outcomes revealed a sizable distinction between the Experiment I class and the Experiment II class. Cognitive ability as measured by the experimental class I average of 85.37 and experimental class II average of 79.58. If the value of sig 0.05, then Ha is acceptable. Cognitive findings sig. (2-tailed) t-test for equality of means on equal variances is assumed to be 0.008. The material for the buffer solution for class XI MIA was found to have a good impact on student learning outcomes when the TGT model using the Ferris wheel was used SMA Negeri 1 Lhokseumawe